Extracellular lactate acts as a metabolic checkpoint and shapes monocyte function time dependently - Schenz, Judith; Heilig, Lena; Lohse, Tim; Tichy, Lucas; Glosse, Katharina; Büttner, Michael; Weigand, Markus A.; Uhle, Florian (Frontiers in immunology, 2021)
Elevated blood lactate levels are frequently found in critically ill patients and thought to result from tissue hypoperfusion and cellular oxygen shortage. Considering the close relationship between immune cell function and intracellular metabolism, lactate is more than a glycolytic waste molecule but able to regulate the immune response. Our aim was to elucidate the temporal and mechanistic effect of extracellular lactate on monocytes. To this end, primary human monocytes and the human monocytic cell line MonoMac6 were stimulated with various toll-like-receptor agonists after priming with Na-L-lactate under constant pH conditions. As readout, cytokine production was measured, real-time assessment of intracellular energy pathways was performed, and intracellular metabolite concentrations were determined. Irrespective of the immunogenic stimulus, short-term Na-lactate-priming strongly reduced cytokine production capacity. Lactate and hexoses accumulated intracellularly and, together with a decreased glycolytic flux, indicate a lactate-triggered impairment of glycolysis. To counteract intracellular hyperglycemia, glucose is shunted into the branching polyol pathway, leading to sorbitol accumulation. In contrast, long-term priming with Na-L-lactate induced cellular adaption and abolished the suppressive effect. This lactate tolerance is characterized by a decreased cellular respiration due to a reduced complex-I activity. Our results indicate that exogenous lactate shapes monocyte function by altering the intracellular energy metabolism and acts as a metabolic checkpoint of monocyte activation.
Gesehen am 14.12.2021